2016
DOI: 10.1111/fare.12191
|View full text |Cite
|
Sign up to set email alerts
|

Historical Oppression and Indigenous Families: Uncovering Potential Risk Factors for Indigenous Families Touched by Violence

Abstract: Violence against Indigenous women in the United States is higher than for any other racial group. Indigenous women tend to rely on families for support and recovery, yet the risk factors related to Indigenous families affected by violence are unknown. Therefore, interviews from a critical ethnography were used to uncover the perspectives of Indigenous women who have experienced intimate partner violence, along with the professionals who serve them, to understand potential risk factors that create vulnerability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
57
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 32 publications
(101 reference statements)
2
57
0
1
Order By: Relevance
“…Using bioecological theory as a framework would also have implications for therapy, particularly community‐based healing that goes beyond individual therapy (Bombay et al, 2014; Brave Heart, ; Evans‐Campbell, ), as well as family therapy that has an intergenerational and historical orientation (Brave Heart, ; Burnette, ; Evans‐Campbell, ). Finally, bioecological theory can inform education, as authors Battiste () and Burnette () have suggested. An appreciation of Indigenous ways of knowing and Indigenous experiences of historical trauma can improve education for Indigenous and non‐Indigenous peoples alike.…”
Section: Bioecological Theory and The Residential Schoolsmentioning
confidence: 99%
See 4 more Smart Citations
“…Using bioecological theory as a framework would also have implications for therapy, particularly community‐based healing that goes beyond individual therapy (Bombay et al, 2014; Brave Heart, ; Evans‐Campbell, ), as well as family therapy that has an intergenerational and historical orientation (Brave Heart, ; Burnette, ; Evans‐Campbell, ). Finally, bioecological theory can inform education, as authors Battiste () and Burnette () have suggested. An appreciation of Indigenous ways of knowing and Indigenous experiences of historical trauma can improve education for Indigenous and non‐Indigenous peoples alike.…”
Section: Bioecological Theory and The Residential Schoolsmentioning
confidence: 99%
“…Finally, as several scholars have suggested, there is a value in “locating personal and family problems in a historical context. Without this, marginalized groups may be further stigmatized and blamed for problems brought on by injustice and oppression” (Burnette, , p. 366).…”
Section: Bioecological Theory and The Residential Schoolsmentioning
confidence: 99%
See 3 more Smart Citations